The coming of Hoole - Lasky, Kathryn (New York : Scholastic, 2006)
Grank raises the royal chick named Hoole deep in the forest in order to protect him; but when an evil warlord attempts to lure Hoole away to kill him, Grank brings Hoole to Beyond the Beyond.
5.3
3-6
Keywords: Owls -- Juvenile fiction; Good and evil -- Juvenile fiction; Owls -- Fiction; Good and evil -- Fiction; Fantasy; Owls -- Fiction; Good and evil -- Fiction; Fantasy fiction; Fantasy fiction